New species, new records and notes in Cerambycidae from Colombia - Nascimento, Francisco E. De L.; Botero, Juan Pablo (Zootaxa, 2018)
A new species from Colombia is described: Ectenessa caputnigra sp. nov. Taxonomic notes on Adiposphaerion rubrum Martins & Napp, 1992, new geographical records to 11 species and the specific locality in Colombia for five species are provided.